KR-delay interval effects in the acquisition of serial skills of different compatibility levels - Palhares, L. R.; Lage, G. M.; Vieira, M. M.; Ugrinowitsch, H.; Benda, R. N. (Journal of Human Movement Studies, 2006)
he present study consisted of two experiments that verified the role of KR-delay interval in the learning of serial skills of different compatibility levels. Thirty-six subjects were randomly distributed into three groups (n=12) in each experiment: no KR-delay interval group (GI), three seconds of KR-delay interval group (G3) and eight seconds of KR-delay interval group (G8). The acquisition phase consisted of two different movement sequences (one for each experiment) in a target time. The transfer (T) and retention (R) tests with the new sequence and target time were applied 3 and 18 minutes after the end of the acquisition, respectively. In the first experiment, G3 had a better performance than GI in both tests (p=0.001) and G8 had a better performance than GI in the second block of transfer tests (p=0.001). In the second experiment, significant differences were detected in the block factor of the acquisition phase [F (l 1.22)= 17.51, p<0.001] and tests [F(4.8)=30.03, p=0.001]. The results indicated that the learning of the task with higher compatibility was affected by the KR-delay interval and suggested that the KR-delay interval is an important variable in the motor learning process.